EFFECT OF STAINLESS STEEL 304 TIG WELDING AMPERE ON STRESS CORROSION CRACKING PHENOMENON - Moch Chamim; Farit Ardiyanto (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2023)
This article discusses the experimental results of stress corrosion cracking grade 304 stainless steel after GTAW welding under environmental corrosion simulation. The corrosion phenomenon that occurs is Stress Corrosion Cracking (SCC). The experimental method is a specimen welded using a current of 55, 60, and 65 Ampere respectively with a gas flow rate of 5 L/min argon shielding gas. The constant tensile loads of 2000 N and 4000 N in the state of the test object immersed for 2 x 24 hours in a solution of HCl + Aquades. Different Ampere and shielding gas flow rate parameters affected the cracks phenomenon. Vickers Hardness and Microstructure were used to evaluate the weld area. The lowest ampere of the weld results in maximum rough cracks from the surface and it's visible on the surface. The increased hardness of the 55 Ampere current specimen indicates a change in structure or phase after welding. The highest ampere produces fine cracks on all surfaces.